Risk markers for acute stroke in Ireland - association of sodium-lithium countertransport (SLC) with vascular disease - Collins, Daniel Ronan (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2002)
The work in this thesis is divided into two parts, an epidemiological study of the risk markers for stroke in an Irish population and a laboratory study of the possible association between sodium lithium countertransport (SLC) and vascular disease. Prior to staiting this work no dedicated acute stroke service was in existence in an Irish teaching hospital and no data had been published on the incidence of major risk factors for stroke in an Irish population. Chapter one of this thesis sets out the background theory to my work and I have set myself a number of objectives in the form of questions which are summarised in chapter two. The methodology employed, and techniques and equipment used are detailed in chapter three.
Keywords: Clinical Pharmacology and Therapeutics, M.D.; M.D. Trinity College Dublin